Communication of Tourism Product; The case of Himara. - ÇANI, Ina; SULI, Hergys; SULI, Dudi (European Journal of Sustainable Development, 2013)
Tourism has and will be generally recognized asthe world’s largest industry. Its growth iscreating rapid social, economic and environmental changes which expect detailedunderstanding and measures to be managed.The market values of tourism can generally berealized by tourism products. This studyaims to explore the potential and communication of tourism product; by studying thecase of Himara, a city in south Albania– the study investigates how communicationtourism product works in a real environment.Nowadays, communication has become a major driver of tourism. Communication intourism is another form of promoting tourism by involving not only linguistic means.Some people traveled specificallyin order to gain a deeper understanding of the culture orheritage of a destination by what they haveheard and read. In order to satisfy tourists’needs and expectations, tourism productstypically attract consumers by thecommunication attributes. People hold a variety of misconceptions about communicationof tourism product. The most common one is its confusion with marketing andpromotion.In general terms, tourism is commonly consideredas a priority sector by Albanian Centraland Local Government. Himara is a small cityin southwest, holding high potential fortourism. It is widely considered an attractive destination of Albanian Riviera; and theoverall objective of this study is to identify the issues and challenges in tourismpromotion facing Himara.